Peripheral osteoma of the mandibular crest: a short case study - Fourcade Arthur; Salmon Benjamin; Le Pelletier François; Ejeil Anne-Laure (EDP Sciences, 2018)
Introduction: Osteoma is a benign slow-growing osteogenic neoplasm characterized by the proliferation of cancellous and/or cortical bone. Jaw bones are seldom affected. Observation: We observed a rare case of a patient with a peripheral mandibular osteoma, which was surgically removed. Comments: Frequently asymptomatic, a peripheral osteoma looks like a bony swelling that may be sessile or pedunculated. Imaging examinations show a well-circumscribed radio-opaque mass. Symptomatic osteomas must be surgically excised and submitted for histological evaluation. Conclusion: Excessive osseous healing following a tooth extraction may explain this rare form of osteoma.